Academic Resiliency of Students Origin from a Broken Home Family - Wulandari, Sri; Nurfarhanah, Nurfarhanah (Consilium, 2023)
Resilience is very important to be able to rise and develop with the pressures experienced by students. Therefore resilience is needed by students who experience a broken home to be able to develop a future orientation that can support their life to be better. The research objective was to determine the level of academic resilience of students from broken home families at Padang 16 Public Middle School in terms of: emotional regulation, impulse control, optimism, ability to analyze problems, empathy, self-efficacy and reaching out . The research was conducted at SMP N 16 Padang, with a quantitative descriptive methodology. The sample of this study was 53 students, using the TIRI instrument (Taufik & Ifdil Inventory Resilience) which was developed from theory (Reivich & Shatté, 2012). Based on the findings, it was concluded that the level of academic resilience of students who came from broken home families was generally in the moderate category with a frequency of 35 and a percentage of 66.04%, meaning that more than half of the students who were the research sample could be said to be resilient.